Rancang Bangun Pembangkit Pulsa Tiga Sensor Ultrasonik Untuk Pendeteksi Kecacatan Beton Berbasis Mikrokontroler - Setyo Swasoko; Abdul Rouf (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
NDT Research conducted to detect any defects on a solid materials. This method is done because not damage the object being tested. Various methods of NDT research also studied, one of which is a multi-transmitter. Multi-transmitter more efficient in scanning objects defective because a more extensive range of sensors. Prioritizing advantages compared with other pulse sources such as AFG, including portable, small radiation, the price relatively cheaper, variety of frequencies that can be generated, and smaller power supplies will be used microcontroller as signal generator.With this concept, generating ultrasonic waves 40kHz emitted by three transmitter input from serial PC to microcontroller and converted into analog signal AD9850 module. Amplitude of the frequency of AD9850 strengthened using LM386, and strengthened again using transfomator ferrite core. And choose sensor, used switches. From research conducted by a few conclusions. Maximum of output voltage AD9850 module is 1.04 V. Maximum output voltage of LM386 is ± 14 V and maximum voltage output of ferrite transformator is ± 170 V. The effective transmitter is SRF04 and maximum input voltage is ± 60 V. Amplitude of wave will be smaller if reflection distance farther, otherwise amplitude increases if the reflection distance is closer.